1983
DOI: 10.2136/sssaj1983.03615995004700060021x
|View full text |Cite
|
Sign up to set email alerts
|

Soil Test Calibration for Establishment of Turfgrass Monostands

Abstract: Little information is currently available relating fertilization and soil fertility to turfgrass establishment response. A field study was conducted on Hagerstown soil (fine, mixed, mesic, Typic Hapludalf) to determine the effects of seedbed applications of P, K, and limestone on establishment rate and quality of monostands of ‘Baron’ Kentucky bluegrass (Poa pratensis L.), ‘Atlanta’ Chewings fescue (Festuca rubra var. commutata Gaud.), and ‘Pennfine’ perennial ryegrass (Lolium perenne L.) Phosphorus applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
15
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 0 publications
2
15
1
Order By: Relevance
“…Under luxury consumption of K, identifying critical tissue K or soil K levels for optimal growth cannot be effectively determined. Critical leaf K concentrations for optimal growth in perennial ryegrass (Lolium perenne L.) have been shown to range from 28 to 38 g kg −1 (Smith et al, 1985) and are among the highest of cool-season turfgrass (Butler and Hodges, 1967;Turner and Waddington, 1983). Potassium can account for as much as 65% of the total ion concentration of the leaf in Kentucky bluegrass (Jiang and Huang, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Under luxury consumption of K, identifying critical tissue K or soil K levels for optimal growth cannot be effectively determined. Critical leaf K concentrations for optimal growth in perennial ryegrass (Lolium perenne L.) have been shown to range from 28 to 38 g kg −1 (Smith et al, 1985) and are among the highest of cool-season turfgrass (Butler and Hodges, 1967;Turner and Waddington, 1983). Potassium can account for as much as 65% of the total ion concentration of the leaf in Kentucky bluegrass (Jiang and Huang, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Potassium can account for as much as 65% of the total ion concentration of the leaf in Kentucky bluegrass (Jiang and Huang, 2001). Critical leaf K concentrations for optimal growth in perennial ryegrass (Lolium perenne L.) have been shown to range from 28 to 38 g kg −1 (Smith et al, 1985) and are among the highest of cool-season turfgrass (Butler and Hodges, 1967;Turner and Waddington, 1983). In such species as perennial ryegrass, their faster leaf extension rate is due in part to their greater leaf turgor caused by accumulation of osmotically active solutes (Thomas, 1990).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…King and Skogley (1969) concluded that the responses of a mixture of Kentucky bluegrass (KB) and red fescue (RF) to the various rates of P were inconsistent. Importantly, Turner and Waddington (1983) were among the few early researchers who reported a positive ground cover response to increasing P levels in the range of 31 to 72 mg kg −1 using Bray No. 1 extractant.…”
mentioning
confidence: 99%
“…The species tested were ‘Baron’ KB, ‘Atlanta’ Chewing's fescue ( Festuca rubra var commutata Gaud. ), and ‘Pennfine’ perennial ryegrass (PR) (Turner and Waddington, 1983). Buffalograss [ Buchloe datyloides (Nutt) Engelm.]…”
mentioning
confidence: 99%